City Branding Strategy to Improve the Competitiveness of Regional Tourism: Study on the City Branding Implementation in Malang Regency - Andriani Kusumawati & Supriono (International Journal of Advanced Science and Technology, 2020)
City branding is a managerial procedure offering cities a different image and identity. It provides the city a clear, positive, unique, and distinguishable image from other cities. However, developing a successful city branding to gain a competitive advantage is a prevalent marketing issue in Malang Regency. The purpose of this study is to analyze the suitability of Malang Regency's city branding strategy utilizing tourism promotion to increase regional competitive advantage. This study used qualitative methods with descriptive and thematic analysis. Data collection was conducted through observation, in-depth interviews, and Focus Group Discussion (FGD). Purposive Sampling and Snowball Sampling methods were utilized to determine samples. The research results exhibited that the socialization experienced constraints due to wide-area coverage and lack of branding experts. In addition, all stakeholders are not involved in the socialization. The investors are prohibited to be involved in the Malang Regency Tourism Village, despite possessing object branding ability and experience.